The study of nuclear structure for some nuclei - Zahraa A. Abdul Muhsin (Iraqi Journal of Physics, 2018)
An analytical form of the ground state charge density distributions for the low mass fp shell nuclei ( 40  A  56 ) is derived from a simple method based on the use of the single particle wave functions of the harmonic oscillator potential and the occupation numbers of the states, which are determined from the comparison between theory and experiment. For investigating the inelastic longitudinal electron scattering form factors, an expression for the transition charge density is studied where the deformation in nuclear collective modes is taken into consideration besides the shell model space transition density. The core polarization transition density is evaluated by adopting the shape of Tassie model together with the derived form of the ground state charge density distribution. In this work, we devote our investigation on 0 3 2 3 1 1    transition of Ti 50 , 0 1 2 1 1 1    transition of Cr 50 and 0 2 2 2 1 1    of Cr 52 nuclei. It is found that the core polarization effects, which represent the collective modes, are essential for reproducing a remarkable agreement between the calculated inelastic longitudinal C2 form factors and those of experimental data.